EFFICIENCY OF FLIGHT SAFETY EXPRESSED BY ANALYTICAL MODEL - Bartoš, Miroslav; Zaremba, Jaroslav; Yakovlieva, Anna (Science-based technologies, 2019)
The implementation of maximum flight safety to supervised flight and airport objects with all modern tracking and control means is currently difficult if we do not know how well the whole structural architecture of these buildings works. The need to increase the level of safety of aeronautical operational objects in various time, space and climatic conditions creates the need to extend the functions of safety devices not only in the field of physical principles but also in the way of their quality assessment. The article deals with the possibility of evaluating process safety management, which is made visible by a multi-level hierarchical structure. High reliability of security management at individual levels does not express the quality of their functions but their ability to solve the submitted tasks. The functions of flight safety systems designed for their practical applicability to aircraft and airports and the adaptation of man-operator create specialized safety complexes whose errors are removed by the operator controlling their functions. Significant in the analysis of the effectiveness and safety of aeronautical systems are the terms in the article that represent inputs to modelling. These terms in principle accept reciprocity distribution of synthetic or natural achievements that are the source of information for managing the safety of the aviation object by the human operator. Together they create reciprocity linked to flight safety limits, which can be verified not only in air transport but also in aviation laboratories, for example. Therefore, each flight safety has a defined range of usability, which is also limited by functional safety and efficiency. It is shown in the paper that the process of increasing the reliability of the hierarchical structure of organizing security must be linked to quality, the criteria of which determine the correlation degree. Efficiency in managing operational flight processes creates a prerequisite for success in any area of controlled flight processes. The quality of organizing a controlled flight process is evaluated by the functional efficiency of managing the entire flight operation.